Influence of Temperature on Electrical Characteristics of Different Photovoltaic Module Technologies - Abdul Rehman Jatoi; Saleem Raza Samo; Abdul Qayoom Jakhrani (International Journal of Renewable Energy Development, 2018)
The aim of this study was to analyse the influence of temperature on electrical characteristics of crystalline and amorphous photovoltaic (PV) modules in outdoor conditions at Nawabshah. The experimental setup was made over the roof of the departmental building. The climatic conditions of site were recorded with the help of HP-2000 Professional Weather Station in three different timings of the day, i.e. morning, noon and evening. The electrical characteristics of the PV modules were recorded with Prova-210 and module temperatures with Prova-830. The maximum intensity of global solar radiation was recorded at noon and ambient temperature in the evening and the relative humidity in the morning hours. It was observed that amorphous module got 0.7°C, 1.0°C and 1.6°C more average temperature than polycrystalline, thin film and monocrystalline modules respectively. The average maximum measured open-circuit voltage was noted from amorphous with 96.7% and minimum from thin film with 81.3% of their respective values on standard conditions, whereas, the average maximum recorded short-circuit current was produced by thin film with 64.9% and minimum by amorphous with 51.4%. The average maximum power was produced by polycrystalline and minimum by amorphous module. It was discovered that the crystalline PV modules gave more fill factor than thin film and amorphous module.Article History: Received January 6th 2018; Received in revised form May 5th 2018; Accepted May 26th 2018; Available onlineHow to Cite This Article: Jatoi, A.R., Samo, S.R. and Jakhrani, A.Q. (2018). Influence of Temperature on Electrical Characteristics of Different Photovoltaic Module Technologies. Int. Journal of Renewable Energy Development, 7(2), 85-91.https://doi.org/10.14710/ijred.7.2.85-91